Socially distanced teaching: The mental health impact of the COVID‐19 pandemic on special education teachers. Issue 3 (15th November 2021) - Cormier, Christopher J.; McGrew, John; Ruble, Lisa; Fischer, Melanie
Abstract: Little is known about the impact of the COVID‐19 pandemic on special education teachers. Of 468 surveyed across the United States, 38.4% met clinical criteria for generalized anxiety disorder, a rate 12.4 times greater than the U.S. population, and 37.6% for major depressive disorder, a rate 5.6 times greater than the population. Race/ethnicity, gender, or school funding was not related to mental health. The impact of the pandemic was moderate to extreme on stress (91%), depression (58%), anxiety (76%), and emotional exhaustion (83%).